Synthesis of dendronized PAMAM grafted ROMP polymers - Islam, Muhammad Nazrul; Cetinkaya, Ilay Ceren; Eren, Tarik; Tulu, Metin (TAYLOR & FRANCIS INC, 2023)
Oxanorbornene cored 0.5, 1.5 and 2.5 generation ester terminated PAMAM dendronized monomers with 2 and 6 carbon-containing alkyl spacer in the middle of oxanorbornene core and dendronized branching were synthesized. Monomers were polymerized through the ring-opening metathesis polymerization (ROMP) technique by using 2nd and 3rd generation Grubbs catalysts to get dendronized ROMP polymers. It was found that Grubbs 3rd generation catalyst works well for 0.5 generation dendronized ROMP polymer whereas Grubbs 2nd generation catalyst works for the higher generation. We also found the linker effect during polymerization as six-carbon linker monomers polymerize with high yield along with higher generation. Finally, dendronized ROMP-based PAMAM encapsulated zero valent Cu nanoparticle was synthesized by using a reducing agent, NaBH4. The catalytic activity of this nanoparticle was further investigated from the reduction of 4-nitrophenol to 4-aminophenol.
Keywords: ROMP; PAMAM; dendrimer encapsulated Cu nanoparticle; catalysis; RING-OPENING METATHESIS; DENDRIMER-ENCAPSULATED NANOPARTICLES; POLYMERIZATION ROMP; POLY(AMIDOAMINE) DENDRIMERS; MACROMONOMER APPROACH; PD NANOPARTICLES; 2ND-GENERATION; CU; FUNCTIONALIZATION; Polymer Science